Heptacarpus littoralis Butler a synonym of Heptacarpus sitchensis (Brandt) (Crustacea: Decapoda: Hippolytidae) - Stamatiou, Lia; Jensen, Gregory C. (Zootaxa, 2004)
Heptacarpus littoralis was differentiated from H. sitchensis based on several characters, including absence of a pterygostomian spine (present in H. sitchensis); distinctly curved propodi of pereopods III-V, and a smaller and more slender body than H. sitchensis. To test whether these differences represent separate species or merely sexual dimorphism within a single species, we collected ovigerous H. sitchensis and raised their larvae to determine if both morphologies would occur within the same progeny. By one year of age many of the shrimp had reached sexual maturity; pterygostomian spines were present on all females but only 27% of the males. Males were also smaller on average than females, and developed the curved propodi and other features characteristic of H. littoralis. Hence, H. littoralis is considered a male form of H. sitchensis and a junior synonym.